San Remo manual on international law applicable to armed conflicts at sea - Doswald-Beck, Louise (Cambridge University Press, 1995)
The San Remo Manual combines a restatement of the law - the first since 1913 - applicable to armed conflicts at sea, with an explanation commenting on the legal basis for the provisions adopted. Compiled by international legal and naval experts, it indicates how States may behave in armed conflict relating to enemy or neutral shipping and aircraft, and to persons captured at sea